Understanding matter: Chemistry workshop-1 - Seymour Rosen (Globe Book, 1977)
This book offers the knowledge of water, air, metal, and salt, for instance. It also examines the small world of the atom, and the many uses of atomic power. Exercises are followed at the end of each lesson